"Everybody Called Her Frank": The Odyssey of an Early Woman Lawyer in New Brunswick - Cahill, Barry (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2011)
In February 1934 Frances Fish was called to the bar of New Brunswick and spent the next forty years practising law in her home town of Newcastle (now City of Miramichi) NB. In 1918 she had been both the first woman to graduate LLB from Dalhousie University and the first woman to be called to the bar of Nova Scotia. Though she initially intended to remain in Halifax, she instead left Nova Scotia almost immediately, abandoning the practice of law altogether. She spent the next fifteen years working as a paralegal in Ottawa and Montreal before returning to New Brunswick and resuming the practice of law. This article is a study of Fish’s career in New Brunswick, framed within the experience of the first women lawyers in Canada, of whom she was the seventh. Résumé En février 1934, Frances Fish a été reçue au Barreau du Nouveau-Brunswick. Pendant les quarante années qui ont suivi, elle a pratiqué le droit dans sa ville natale, Newcastle (qui fait maintenant partie de la ville de Miramichi), au Nouveau-Brunswick. En 1918, elle a été la première femme à obtenir un baccalauréat en droit de la Dalhousie University et la première femme reçue au Barreau de la Nouvelle-Écosse. Bien qu’elle avait, au début, l'intention de rester à Halifax, elle a quitté la Nouvelle-Écosse presque immédiatement après ses études, abandonnant complètement la pratique du droit. Elle a travaillé comme technicienne juridique pendant quinze ans avant de revenir au Nouveau-Brunswick et de reprendre la pratique du droit. Le présent article est une étude de la carrière de Fish au Nouveau-Brunswick en tant que l’une des premières femmes juristes du Canada, soit la septième.